2022
DOI: 10.3389/fpsyt.2022.883371
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Optimal Motion of Android Robots for the Ease of Communications Among Individuals With Autism Spectrum Disorders

Abstract: Android robots are employed in various fields. Many individuals with autism spectrum disorders (ASD) have the motivation and aptitude for using such robots. Interactions with these robots are structured to resemble social situations in which certain social behaviors can occur and to simulate daily life. Considering that individuals with ASD have strong likes and dislikes, ensuring not only the optimal appearance but also the optimal motion of robots is important to achieve smooth interaction and to draw out th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
2
5
0
2
Order By: Relevance
“…In this study, among the self-administered questionnaire variables, the sensory profile would have a contribution to robot perception of affect and engagement. Kumazaki et al (20) revealed that in an interview setting with an android robot, the sensory profile is an important factor for estimating the attitude of individuals with ASD toward android robots, which is in line with the results of this study. Kim et al (48) suggested that improving audio-based emotion estimation for individuals with ASD could allow the robotic system to properly assess the engagement of individuals, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, among the self-administered questionnaire variables, the sensory profile would have a contribution to robot perception of affect and engagement. Kumazaki et al (20) revealed that in an interview setting with an android robot, the sensory profile is an important factor for estimating the attitude of individuals with ASD toward android robots, which is in line with the results of this study. Kim et al (48) suggested that improving audio-based emotion estimation for individuals with ASD could allow the robotic system to properly assess the engagement of individuals, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Kumazaki et al. ( 20 ) revealed that in an interview setting with an android robot, the sensory profile is an important factor for estimating the attitude of individuals with ASD toward android robots, which is in line with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We used A-Lab android ST ( Figure 1 ) ( 41 , 42 ) (A-Lab Co., Ltd., Chiyoda-ku, Tokyo, Japan), which is a female android robot with an appearance similar to that of a real person. Its motor system consisted of air cylinders and rotary actuators with the 19 degrees of freedom (DoFs) to produce flexible and silent motions: 12 for facial expression such as smiling and brow movements, 4 for head motion such as nodding, and 3 for upper body motion such as breathing.…”
Section: Methodsmentioning
confidence: 99%